2015
DOI: 10.1021/acs.iecr.5b03562
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Earth Metal Modified H-Mordenites. Their Catalytic Properties in the Isopropylation of Biphenyl

Abstract: Alkaline earth metal modification of H-mordenite (MOR) was examined in the isopropylation of biphenyl (BP). Of interest was the chemical and textural changes on catalytic properties as a result of the modification. At low loadings of 0.2− 0.5 mmol/g of the metals, the isomerization of 4,4′-diisopropybiphenyl (4,4′-DIPB) was effectively prevented at temperatures as high as 300 °C, resulting in high selectivities for 4,4′-DIPB. Metals reduce the acid amounts by low loadings, and deactivate external acid sites. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…XRD diffraction peaks for MgO were not detected for any of the magnesium-impregnated zeolites (2θ = 37.0, 43.0, 62.4, 74.8 and 78.7° [33,34]), meaning that any formed MgO entities are either amorphous or small enough in size to escape XRD detection. A reduction in intensity of the zeolite diffraction peaks has been noticed by several authors when impregnating Y, ZSM-5 and MOR zeolites with up to 15 wt.% of magnesium [31,[35][36][37][38]. The same authors also observed that MgO diffraction peaks were absent even at the highest percentages of magnesium.…”
Section: Catalytic Testmentioning
confidence: 57%
See 1 more Smart Citation
“…XRD diffraction peaks for MgO were not detected for any of the magnesium-impregnated zeolites (2θ = 37.0, 43.0, 62.4, 74.8 and 78.7° [33,34]), meaning that any formed MgO entities are either amorphous or small enough in size to escape XRD detection. A reduction in intensity of the zeolite diffraction peaks has been noticed by several authors when impregnating Y, ZSM-5 and MOR zeolites with up to 15 wt.% of magnesium [31,[35][36][37][38]. The same authors also observed that MgO diffraction peaks were absent even at the highest percentages of magnesium.…”
Section: Catalytic Testmentioning
confidence: 57%
“…MgO particles were also not observable by TEM, as the contrast between the elements in the zeolite framework and the metal oxide species was insufficient [36]. However, by coupling EDS analysis to TEM it was possible to investigate how homogeneous was the dispersion of MgO on the different zeolite structures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%